When the South emulates the North: energy policies and nationalism in the twentieth century - Madureira, Nuno Luis (Contemporary European History, 2008)
Differences in natural endowments, in geographical conditions and in per capita income set up an historical bifurcation between northern states, with abundant renewable hydrological resources, and less well-endowed southern states. While the first embraced a model of electricity adding, with the embodiment of this form of energy in capital goods and intermediate goods, the second followed a path of electricity substitution, with mixed strategies of replacing inputs in established sectors of industry, public utilities, transport and private consumption. This article examines the different plans for and achievements of economic nationalism in the twentieth century and its consequences, discussing the possibility of reproducing in Portugal the pattern of the stimulus to industrial manufacturing of cheap electricity.